2019
DOI: 10.1167/iovs.18-26297
|View full text |Cite
|
Sign up to set email alerts
|

Outer Retinal Structure and Function Deficits Contribute to Circadian Disruption in Patients With Type 2 Diabetes

Abstract: PURPOSE. Light transmitted by retinal photoreceptors provides the input for circadian photoentrainment. In diabetes, there is a high prevalence of circadian and sleep disruption but the underlying causes are not well understood. Patients with diabetes can exhibit dysfunctional photoreceptors but their role in circadian health is not known. Here we quantify photoreceptor function and contributions to circadian health and sleep in patients with diabetes without diabetic retinopathy and healthy controls. METHODS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 56 publications
4
25
1
Order By: Relevance
“…Recently, Dumpala et al (12) reported the outer retinal thinning and dysfunction in a small number of patients with type 2 diabetes and inferred that outer retinal structure and function deficits contribute to the sleep disruption in type 2 diabetes. However, they determined the thickness of total outer retina and did not directly associate the individual components of sleep disorder with the thickness at ETDRS grids of each outer retinal layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Dumpala et al (12) reported the outer retinal thinning and dysfunction in a small number of patients with type 2 diabetes and inferred that outer retinal structure and function deficits contribute to the sleep disruption in type 2 diabetes. However, they determined the thickness of total outer retina and did not directly associate the individual components of sleep disorder with the thickness at ETDRS grids of each outer retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy and neuropathy influence the thickness of the macular neuroretinal layers (8,9) and sleep disorder (10,11); however, these have not been investigated in detail. Recently, Dumpala et al (12) reported that the thinning and dysfunction of the outer retina in the small number of patients with type 2 diabetes may contribute to poor sleep behavior. However, they did not find a significant direct association between the thicknesses at the individual grids defined by the Early Treatment Diabetic Retinopathy Study (ETDRS) of outer retinal layers and the components of sleep disorder.…”
Section: Introductionmentioning
confidence: 99%
“…31 The importance of RPE to DR development depends on the photoreceptor abnormalities present early in the DR pathogenesis. [32][33][34][35] Another important feature of increasing outer retinal barrier resistance is the fluid accumulation in the subretinal space, particularly in the macular area, [36][37][38][39] which is a hallmark of diabetic macular edema and has important clinical relevance. Thus, the RPE role in DR deserves further investigation and could represent a possible site for novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Light responses depending on generalised medical and psychiatric status [ 176 , 177 , 178 , 179 ] and medication [ 180 ]…”
Section: Figurementioning
confidence: 99%
“…Light responses depending on generalised medical and psychiatric status [176][177][178][179] and medication [180] (ii) Genetic differences: (iv) Mixed physiological/behavioural effects:…”
mentioning
confidence: 99%